Common Challenges in the Prehospital Management of Mass-Casualty Incidents: A Systematic Integrative Review - Hugelius, Karin; Becker, Julia (Prehospital and disaster medicine, 2024)
Mass-casualty incidents (MCIs) place extraordinary demands on prehospital medical response. However, there remains limited evidence on best practices in managing MCIs, and therefore, there is a need to systematically synthetize experiences from them to build further evidence. This study aimed to analyze common challenges in prehospital MCI management. Seventeen case studies or reports describing 15 MCIs (ie, terrorist attacks, chemical incidents, traffic accidents, weather-related incidents, and fires) were subject to a systematic integrative review. Common challenges in prehospital MCI management include victim and responder safety- and security-related issues; the need to develop and communicate situational awareness; to develop and apply a prehospital response plan; the ability to deliver care under severe circumstances; and the need for an extended prehospital medical response management strategy. Resilient prehospital MCI response demands both a clear strategy and improvisation and should be integrated into the overall medical response strategy. Responders must understand the main concepts of prehospital MCI management, have a situational awareness that foresees the event's medical consequences, and have the experience required to interpret the situation. Emergency Medical Services (EMS) personnel and medical incident commanders require specific training and mental preparation to be able to provide care under severe security threats, to improvise beyond routines and guidelines, and to provide care in ways different from their everyday work.